2020
DOI: 10.1038/s41598-020-71787-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of airborne particles and bioaerosols concentrations in a waste recycling environment in Brazil

Abstract: This study aims to assess the concentrations of size-fractioned particle mass (PM1.0, PM2.5, PM4.0, PM10) and number (PNC0.3, PNC0.5, PNC1.0, PNC2.5), bacteria, and fungi in a Materials Recycling Facility (MRF) in Brazil. The measurements were performed inside the waste processing shed (P1) and in the outdoor environment (P2) during working days in winter and spring of 2017, and summer of 2019. A total of 2,400 min of PM, 1,440 min of PNC, and 216 samples of bioaerosols were collected in the morning and aftern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 82 publications
1
14
0
Order By: Relevance
“…Cyprowski et al ( 2019 ) reported the highest concentration of total viable bacteria in summer (temperature range 10–29.1 °C), while the levels of gram-negative bacteria were highest in autumn (temperature range 0.8–10 °C) in Poland. Similarly, Fernanda et al ( 2020 ) analysed the bioaerosol levels in landfill sites located in Brazil for all three seasons and observed highest concentrations of airborne bacteria in summer and fungi in spring. Madhwal et al ( 2020 ) also reported peak in fungal and bioaerosol concentrations during monsoon (temperature 29.14 ± 2.38 °C and RH 67.31 ± 8.64%), while winter (temperature 17.46 ± 3.0 °C and RH 34.83 ± 8.57%) witnessed a dip in the levels of bioaerosols released from Indian MSW landfill.…”
Section: Temporal Variations In Bioaerosol Concentrationsmentioning
confidence: 97%
See 1 more Smart Citation
“…Cyprowski et al ( 2019 ) reported the highest concentration of total viable bacteria in summer (temperature range 10–29.1 °C), while the levels of gram-negative bacteria were highest in autumn (temperature range 0.8–10 °C) in Poland. Similarly, Fernanda et al ( 2020 ) analysed the bioaerosol levels in landfill sites located in Brazil for all three seasons and observed highest concentrations of airborne bacteria in summer and fungi in spring. Madhwal et al ( 2020 ) also reported peak in fungal and bioaerosol concentrations during monsoon (temperature 29.14 ± 2.38 °C and RH 67.31 ± 8.64%), while winter (temperature 17.46 ± 3.0 °C and RH 34.83 ± 8.57%) witnessed a dip in the levels of bioaerosols released from Indian MSW landfill.…”
Section: Temporal Variations In Bioaerosol Concentrationsmentioning
confidence: 97%
“…Optimum microclimatic conditions for the proliferation of bacteria and fungi vary significantly. Most researchers from countries with temperate or continental climates reported higher fungal aerosols during the warm season compared to the cold season (Cyprowski et al 2019 ; Fernanda et al 2020 ; Fraczek et al 2017 ; Madhwal et al 2020 ). The humid environment supports maximum growth of bacteria, while fungi proliferate quickly in a dry environment (Hu et al 2020 ).…”
Section: Temporal Variations In Bioaerosol Concentrationsmentioning
confidence: 99%
“…Animals, plants insects, and mites can produce biological allergens such as house dust, pets, and mold in indoor areas can trigger various allergic reactions and may be responsible for respiratory problems (WHO, 1988 ). Poor indoor air quality is also related to several health risks in waste pickers (Wikuats et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al (2021) reported that the concentrations of airborne fungi in landfill ranged from 376 to 9318 CFU/m 3 . Wikuats et al (2020) found that the concentrations of bacteria bioaerosol and fungal bioaerosol emitted from a material recycling facility were 1088.8AE825.2 and 2738.3AE1381.3 CFU/m 3 , respectively. The spread of bioaerosols is one of the possible ways to spread diseases, especially in the worldwide COVID-19 pandemic this year, which has made people more aware and vigilant of the generation and harm of bioaerosols (Mutuku et al, 2020).…”
Section: H I G H L I G H T Smentioning
confidence: 97%